C9orf72 Hexanucleotide Repeat in Huntington-Like Patients: Systematic Review and Meta-Analysis - Alva-Diaz, Carlos; Alarcon-Ruiz, Christoper A.; Pacheco-Barrios, Kevin; Mori, Nicanor; Pacheco-Mendoza, Josmel; Traynor, Bryan J.; Rivera-Valdivia, Andrea; Lertwilaiwittaya, Pongtawat; Bird, Thomas D.; Cornejo-Olivas, Mario (Frontiers in Genetics, 2020)
Introduction: Patients with Huntington-Like disorders (HLD) comprise a variety of allelic disorders sharing a Huntington phenotype. The hexanucleotide repeat expansion of the C9orf72 gene could explain part of the HLD etiology. Our aim was to conduct a systematic review and meta-analysis looking for the frequency of the hexanucleotide repeat expansion of the C9orf72 gene in patients with Huntington-Like disorders. Methods: The protocol was registered on the International Prospective Register of Systematic Reviews database (PROSPERO) (registration number: CRD42018105465). The search was carried out in Medline, Scopus, Web of Science, and Embase in April 2018. Observational studies reporting patients with HLD carrying the hexanucleotide repeat expansion in the C9orf72 gene were selected and revised; this process was carried out in duplicate. The cutoff threshold for considering the hexanucleotide expansion as a pathogenic variant was equal to or greater than 30 G4C2 repeats. Pooled frequency and 95% CI were calculated using random-effects models. Results: Nine out of 212 studies were selected, reporting a total of 1421 affected individuals with HLD. Among them, 24 individuals carried C9orf72 expansion, representing a 1% (95%CI: 0-2%, I2=55.3%) of the pooled frequency. Seven selected studies came from European centers, one was reported at a US center, and one came from a South-African center. Individuals carrying the C9orf72 repeat expansion experienced psychiatric and chorea-type motor and parkinsonism symptoms. Conclusions: The estimated frequency of C9orf72 unstable hexanucleotide repeat expansion in patients with HLD is very low.